THE IMPACT OF ECONOMIC GROWTH ON POVERTY REDUCTION IN THE REPUBLIC OF SERBIA - Roganović, Milijana; Stankov, Biljana (International Journal of Economic Practice and Policy, 2019)
A large number of countries face serious poverty-related problems, regardless of the level of economic development. Poverty, as a multidimensional phenomenon, on the one hand, implies income insufficiency to meet basic living needs, while, on the other hand, it also applies to various aspects of human rights, such as: the inability to recruit a new staff, inadequate housing conditions and inadequate access to social protection, health, education and communal services. Due to a significant reduction in economic activities in the Republic of Serbia, there is a decline in the living standard of the population and the simultaneous growth of poverty. The aim of the research is precisely to prove the existence of a statistically significant correlation between the rate of economic growth and the poverty rate in the Republic of Serbia. The results of the research indicate that the accelerated economic growth and development in the country certainly contribute to the increase of employment, i.e. to the increase in the living standard of the population, and consequently to the reduction of the poverty rate. The authors point out that the goals and tasks related to achieving fast and dynamic economic growth and development must be key elements of the strategy of economic development of the Republic of Serbia. Also, authors suggest various measures to increase employment raise living standards and reduce poverty rates.